Training in social research skills from school: An experience at colegio Cundinamarca IED, Bogotá 2013 -2019 - Guzmán Cueto, Marta Cecilia; Pulgar Suárez, Luis Alejandro (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2020)
The article presents a training experience in social research skills, carried out with Cycle V students in Ciudad Bolívar, a town that, due to its conditions, facilitates the possibility of building new learning from the experienced social realities. The objective is to implement a pedagogical process of training in social research with students, from an interdisciplinary perspective whose starting point is the social sciences. The results allow us to highlight the importance of social research at school, from its possibility of generating forms of approach to the socio-structural problems of the communities.